Perancangan Sistem Informasi Penjualan Berbasis Web di PT. MARKTEL - Anggraeni, Olivia Putri; Karyadi, Karyadi; Abdussalaam, Falaah (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2023)
Information systems are needed in every company to facilitate fast and accurate data processing. One of them is a sales information system currently used at PT. MARKTEL still has processes that have not been computerized. To meet these information needs, especially to deal with data processing problems, report generation and systems that have not worked as expected, companies need a computer-based information system. The system development method in this study uses the waterfall method which has a systematic and clear flow so that the system development is more detailed. The waterfall method is a structured modeling-based method consisting of Flowmaps, Context Diagrams, Level 0 Data Flow Diagrams (DFD) and Entity Relationship Diagrams (ERD). In designing and implementing the program, the author uses the PHP programming language with MySQL database. The existence of a web-based sales information system at PT.MARKTEL is expected to simplify and speed up data processing and report generation and can minimize errors so that company goals can be achieved optimally.